1996
DOI: 10.1007/bf01477260
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of the tibial tubercle for patellofemoral pain syndrome

Abstract: One hundred patients were operated on by the Maquet procedure for chondromalacia patellae. All of them were first re-examined after a mean follow-up of 4 years, and 65 of them re-examined after a mean follow-up of 11 years (range, 8-15 years). The pain score improved significantly after the operation and remained unchanged with longer follow-up. The success rate was only 62% at both follow-ups. Outerbridge grade IV chondral lesions at the time of surgery were associated with a significant improvement of the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 14 publications
3
33
0
Order By: Relevance
“…Our experience, like that of other authors [10,20,30,31,43,50], has confirmed that appropriate indication and accurate surgical technique facilitate good clinical results in the treatment of degenerative patellofemoral chondral lesions (Table 5). However, direct comparison of our results with published results is limited by the heterogeneity of cohorts [3,10,15,19,55], the exact procedures used, and the outcome instruments used [8,10,20,26,50]. Consistent with the findings of others [3,26], we found age, gender, body mass index, duration of symptoms, preoperative patellofemoral narrowing, or location of chondral lesion did not influence the clinical outcome scores.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Our experience, like that of other authors [10,20,30,31,43,50], has confirmed that appropriate indication and accurate surgical technique facilitate good clinical results in the treatment of degenerative patellofemoral chondral lesions (Table 5). However, direct comparison of our results with published results is limited by the heterogeneity of cohorts [3,10,15,19,55], the exact procedures used, and the outcome instruments used [8,10,20,26,50]. Consistent with the findings of others [3,26], we found age, gender, body mass index, duration of symptoms, preoperative patellofemoral narrowing, or location of chondral lesion did not influence the clinical outcome scores.…”
Section: Discussionsupporting
confidence: 86%
“…However, direct comparison of our results with published results is limited by the heterogeneity of cohorts [3,10,15,19,55], the exact procedures used, and the outcome instruments used [8,10,20,26,50]. Consistent with the findings of others [3,26], we found age, gender, body mass index, duration of symptoms, preoperative patellofemoral narrowing, or location of chondral lesion did not influence the clinical outcome scores. However, we found outcomes correlated with preoperative clinical status and grade of chondral lesion (Table 3).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…A bone block is then placed in the osteotomy site to displace this loosened bone wedge anteriorly (Fig. 6) [13]. The EllmslieTrillat procedure consists of a complete osteotomy of the tibial tuberosity at its base and medial screw fixation (Fig.…”
Section: Recurrent Patellar Dislocation or Subluxationmentioning
confidence: 99%